2020
DOI: 10.1002/chem.202002351
|View full text |Cite
|
Sign up to set email alerts
|

Dinuclear Complexes of Flexidentate Pyridine‐Substituted Formazanate Ligands

Abstract: The utility of flexidentate pyridyl‐substituted formazanate ligands for assembling dinuclear coordination complexes with iridium(III) and/or platinum(II) building blocks is demonstrated herein. The dinuclear complexes are prepared either via a stepwise strategy, adding one metal unit at a time, or via one‐pot self‐assembly. Eight of the new complexes, including both mononuclear precursors and dinuclear products, are structurally characterized by single‐crystal X‐ray diffraction and NMR spectroscopy, revealing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 48 publications
3
11
0
2
Order By: Relevance
“…Table 1 also summarizes previous iridium complexes that we reported that contain pyridylformazan Fz coordinated to iridium through the pyridine ring. 28 The first reduction potential in nickelcoordinated 2 is very similar to that of the previously reported complex Ir(F 2 ppy) 2 (FzH)(Cl), 28 in which the formazanate core is not coordinated to a metal, suggesting little contribution of the nickel center to the LUMO. In these complexes with a single formazanate bridging ligand, only a single reduction wave is observed, in contrast to the two waves observed in 1−5, further underscoring the conclusion that the two waves represent successive reduction of the two formazanates.…”
Section: ■ Results and Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Table 1 also summarizes previous iridium complexes that we reported that contain pyridylformazan Fz coordinated to iridium through the pyridine ring. 28 The first reduction potential in nickelcoordinated 2 is very similar to that of the previously reported complex Ir(F 2 ppy) 2 (FzH)(Cl), 28 in which the formazanate core is not coordinated to a metal, suggesting little contribution of the nickel center to the LUMO. In these complexes with a single formazanate bridging ligand, only a single reduction wave is observed, in contrast to the two waves observed in 1−5, further underscoring the conclusion that the two waves represent successive reduction of the two formazanates.…”
Section: ■ Results and Discussionsupporting
confidence: 81%
“…All of the trimetallic complexes 2−5 were synthesized in CH 2 Cl 2 by mixing complex 1 and the respective iridium dimer in a 1:1 ratio. Also shown in Scheme 1, the trimetallic complexes can alternatively be synthesized by first coordinating the free pyridylformazan to iridium, accessing a precursor described in our previous work on these ligands, 28 and then treating with nickel(II) acetate. Although the target compounds were formed by this route, we also observed the formation of insoluble side products, making it difficult to purify the desired compounds and isolate them in a satisfactory yield.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations